Normative data on a Malay version of the Boston Naming Test - Sandra Van Dort,; Etaine Vong,; Rogayah A.Razak,; Rahayu Mustaffa Kamal,; Hooi, Poh Meng (penerbit ukm, 2007)
This paper aims to describe a Malay version of the Boston Naming Test (MBNT) and its normative data. The M-BNT follows closely the general administration procedures of the original Boston Naming Test (BNT) but is different in terms of item content. A total of 29 items from the original 60 items on the test were deemed culturally and linguistically valid for the Malay population and were thus retained. A total of 41 additional items were added to make a total list of 70 items for pilot testing. These items were first vetted by a panel of experts and then trialed on a sample of 40 Malay adults. Based on the item analysis from the pilot study, the M-BNT was reduced to a 50 item test. This was administered to 230 normal Malay subjects in five age groups (20 – 29 years, 30 – 39 years, 40 – 49 years, 50 – 59 years, and 60 – 69 years), split into two main educational levels (i.e. < 12 years of education, and 12 years or more) and across gender. The Malay subjects were chosen representative of the four major geographical regions in West Malaysia. Initial normative data was computed according to the five age groups and two educational levels. It is hoped that the M-BNT will become a test useful in the identification of patients with an expressive language word-finding disorder.